Obesity studies in the circumpolar Inuit:a scoping review - Galloway, Tracey; Blackett, Hilary; Chatwood, Susan; Jeppesen, Charlotte; Kandola, Kami; Linton, Janice; Bjerregaard, Peter (International Journal of Circumpolar Health, 2012)
Among circumpolar populations, recent research has documented a significant increase in risk factors which are commonly associated with chronic disease, notably obesity.